Towards modelling intergranular stress-corrosion cracks using experimentally obtained grain topologies - Simonovski, I; Cizelj, L; Marrow, T; Quinta Da Fonseca, J; King, A (2010)
Predicting the effects of material aging in view of development of intergranular damage is of particular importance in a number of nuclear installations and especially in structural integrity assessments of critical components in energy generating power plants. Since the damage is initialized on small length scales, detailed multiscale models should be employed to tackle the problem. However, the complexity of such models is high due to the need of incorporating micro structural features. In line of this the research group from Jožef Stefan Institute and The University of Manchester joined forces and knowledge in development of such detailed multiscale models. The basic idea was to pair the knowledge of advanced experimental techniques of The University of Manchester group with the knowledge of advanced microstructure modelling techniques of the group at Jožef Stefan Institute. The presented paper proposes a novel approach for intergranular crack modelling whereby a state-of-the-art X-ray diffraction contrast tomography technique is used to obtain 3D topologies and crystallographic orientations of individual grains in a stainless steel wire and intergranular stress corrosion cracks. As measured topologies and orientations of individual grains are then reconstructed within a finite element model and coupled with advanced constitutive material behaviour: anisotropic elasticity and crystal plasticity. Due to the extreme complexity of grain topologies, transferring this information into the finite element model presents a challenging task. The feasibility of the proposed approach is presented. Difficulties in building a finite element model are discussed. Preliminary results of the analyses are also given. Copyright © 2009 by ASME.